Rabindranatha Tagore's Humanistic Spiritual Thoughts - Study Based On Gitanjali - Tharsiga, G. (University of Jaffna, 2018)
Rabindranath Tagore’s thoughts are important among the contemporary Indian philosophers. The Contemporary Indian philosophy dose not exploited out of the tradition and at the same time seems to have made some changes in the context of time. Contemporary Indian philosophers are played a wide role in the preserving the spiritualized ideas and contributed to understand the significance and special features to other communities. This study researches the spiritual thoughts in contemporary India, presented by the Rabindranath Tagore through his poetry Gitanjiali. Qualitative technics were used for this study. Here, Gitanjali book was used as the primary data and books, research articles and website information related to Rabindranath Tagore’s Gitanjali used as secondary data. Analytical methodology, descriptive methodology and comparative methodologies are used as research methods. Here the study concludes that spirituality is built through humanity.
Keywords: contemporary indian philosophy; gitanjaili; humanity; spiritual thoughts; rabindranath tagore